Respuesta :
Answer:
[tex]\large\boxed{A.\ y^3}[/tex]
Step-by-step explanation:
[tex]\text{Use}\ \dfrac{a^m}{a^n}=a^{m-n}\\\\\dfrac{y^{10}}{y^7}=y^{10-7}=y^3[/tex]
[tex]\text{Other method:}[/tex]
[tex]\text{We know:}\ a^n=\underbrace{a\cdot a\cdot a\cdot...\cdot a}_{n}\\\\y^{10}=\underbrace{y\cdot y\cdot y\cdot y\cdot y\cdot y\cdot y\cdot y\cdot y\cdot y}_{10}\\\\y^7=\underbrace{y\cdot y\cdot y\cdot y\cdot y\cdot y\cdot y}_7}[/tex]
[tex]\dfrac{y^{10}}{y^7}=\dfrac{y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup\cdot y\cdot y\cdot y}{y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup\cdot y\!\!\!\!\diagup}=y\cdot y\cdot y=y^3[/tex]